Coffee Adulteration: More than Two Decades of Research. (3rd March 2016) - Toci, Aline Theodoro; Farah, Adriana; Pezza, Helena Redigolo; Pezza, Leonardo
ABSTRACT: Coffee is a ubiquitous food product of considerable economic importance to the countries that produce and export it. The adulteration of roasted coffee is a strategy used to reduce costs. Conventional methods employed to identify adulteration in roasted and ground coffee involve optical and electron microscopy, which require pretreatment of samples and are time-consuming and subjective. Other analytical techniques have been studied that might be more reliable, reproducible, and widely applicable. The present review provides an overview of three analytical approaches (physical, chemical, and biological) to the identification of coffee adulteration. A total of 30 published articles are considered. It is concluded that despite the existence of a number of excellent studies in this area, there still remains a lack of a suitably sensitive and widely applicable methodology able to take into account the various different aspects of adulteration, considering coffee varieties, defective beans, and external agents.